Between coercion and consent: the politics of "Cooperative Governance" at a time of "Austerity Localism" in London. Issue 9 (21st October 2017) - Penny, Joe
ABSTRACT: At a time of "austerity localism", this paper explores how local authorities in London, England, are simultaneously addressing the dual pressures of delivering fiscal retrenchment and of enrolling citizens in new participatory public service arrangements, asking whether "these trends pull against one another, in opposite directions, or whether they are the tough and tender dimensions of a singular process: austerian management" Drawing on empirical research into the London Borough of Lambeth's Cooperative Council agenda, as well as Foucauldian and Gramscian critiques of participatory network governance theories and practice, this paper shows how participatory forms of governance can be folded into the logic of hierarchy and coercion through various governmental technologies of performance and agency (consent), and through tactics of administrative domination (coercion). As budget cuts continue to affect local government in England, this paper concludes that although small experiments in participatory governance may persist, the dominant mode of governance is likely to shift towards more hierarchical and coercive forms.